2017
DOI: 10.21873/anticanres.11557
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis of a Pseudoangiomatous Pleomorphic/Spindle Cell Lipoma

Abstract: Several acquired genomic aberrations were found in the tumor. Among them was loss of chromosome 13 material. Results confirm the (cyto)genetic similarity between pseudoangiomatous pleomorphic/spindle cell lipoma and spindle cell lipomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…In the existing studies, lncRNA DLEU1 as a new research focus, is closely related to the tumor. Most studies have revealed that there is deletion of DLEU1 gene that maps to a region at chromosoma 13q14.3 in some solid tumors and hematopoietic malignancies, such as atypical or classical spindle cell lipomas, chronic lymphocytic leukemia, and small lymphocytic lymphoma . In addition, lncRNA DLEU1 can also work as an oncogene in gastric cancer and ovarian carcinoma .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the existing studies, lncRNA DLEU1 as a new research focus, is closely related to the tumor. Most studies have revealed that there is deletion of DLEU1 gene that maps to a region at chromosoma 13q14.3 in some solid tumors and hematopoietic malignancies, such as atypical or classical spindle cell lipomas, chronic lymphocytic leukemia, and small lymphocytic lymphoma . In addition, lncRNA DLEU1 can also work as an oncogene in gastric cancer and ovarian carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have revealed that there is deletion of DLEU1 gene that maps to a region at chromosoma 13q14.3 in some solid tumors and hematopoietic malignancies, such as atypical or classical spindle cell lipomas, chronic lymphocytic leukemia, and small lymphocytic lymphoma. [6][7][8][9][10] In addition, lncRNA DLEU1 can also work as an oncogene in gastric cancer and ovarian carcinoma. 11,12 However, the role and effect mechanism of lncRNA DLEU1 in endometrial carcinoma remain unknown.…”
mentioning
confidence: 99%
“…Although the deletion of ch13q14 where human DLEU1 gene is localized in certain types of cancers supports the notion that DLEU1 is a tumor suppressor [ 1 4 ], the absence of DLEU1 gene in mouse ch13q14, together with the presence of at least several other tumor suppressor genes in this chromosomal locus, dampen the significance of loss of DLEU1 expression in tumorigenesis [ 23 , 24 ]. In contrast, increasing studies focusing on DLEU1 presented convincing evidence that DLEU1 is a pan-cancer oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies demonstrate aberrant expression of long non-coding RNAs (lncRNAs) in cancers, supporting their role as biomarkers for cancer diagnosis and prognosis. The lncRNA deleted in lymphocytic leukemia 1 (DLEU1) is encoded by a gene localized in chromosome 13q14.3, a chromosomal region frequently deleted in spindle cell lipoma and other hematological malignancies [ 1 4 ], suggesting it may be a tumor suppressor. However, recent studies reveal oncogenic activities of DLEU1: it is up-regulated in a panel of human cancers, correlates with worse prognosis, and promotes various malignant phenotypes [ 5 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, DLEU2 has been reported to be abnormally expressed in many malignant tumors. For example, DLEU2 is downregulated in chronic lymphocytic leukemia (CLL) [ 6 ], pleomorphic liposarcoma (PL) [ 9 ], Pseudoangiomatous Pleomorphic/Spindle Cell Lipoma [ 10 ], pediatric AML [ 8 ], and breast cancer (BC) [ 11 ]. However, most reports have shown upregulation of DLEU2 in cancers, including endometrial cancer(EC) [ 12 ], renal clear cell carcinoma(ccRCC) [ 13 ], esophageal cancer (ESCA) [ 14 ], pancreatic cancer (PC) [ 15 ], glioma [ 16 ], gastric cancer(GC) [ 17 ], non-small cell lung cancer (NSCLC) [ 18 ], thyroid cancer(TC) [ 19 ], and prostate cancer (PCa) [ 20 ].…”
Section: Dleu2 In Cancermentioning
confidence: 99%